Do We Need a New Conception of Authorship? - Balganesh, Shyamkrishna (The Columbia Journal of Law & the Arts, 2020)
Here’s the core idea that I want to suggest: that one of the concerns that we have with conceptual art going forward, and with the question of copyrightability, is that copyright law, for a really long time now, has had a nascent and unstated theory of authorship that connects to the way in which we conceptualize the connection between inputs and outputs, agency in the real world, and the nature of the human connection to the work—and that these works of conceptual art are calling that theory into question. And part of the concern is that this test and this conception, being unstated—when we take a step back to try and understand how we might update it or liberate it from these conceptions, we have a hard time wrestling with it, to nail it down. And so, what I want to leave you with is the question of whether it’s time to update our traditional conception of authorship.